Phytochemical Screening and Antibacterial Activity of Jatropha multifida Leaf Extract Against Pseudomonas aeruginosa - Manik, Umi Chairani; Rahmadani, Rahmadani (Pustaka Media Publishing, 2025)
The increasing prevalence of antibiotic-resistant bacteria has encouraged the exploration of alternative antibacterial agents derived from medicinal plants. Jatropha multifida L., commonly known as the Bethadine plant, has been traditionally used for treating infections and wounds due to its bioactive phytochemical compounds. This study aimed to evaluate the antibacterial activity of Jatropha multifida leaf extract against Pseudomonas aeruginosa and to identify the presence of secondary metabolites through phytochemical screening. The study employed an experimental laboratory design. Jatropha multifida leaves were processed into simplicia powder and extracted using the maceration method. Phytochemical screening was performed to detect the presence of alkaloids, flavonoids, saponins, steroids/triterpenoids, and tannins. The antibacterial activity of the extract was tested against Pseudomonas aeruginosa using the agar disc diffusion (Kirby–Bauer) method at concentrations of 10%, 20%, 30%, 40%, and 50%. Chloramphenicol and dimethyl sulfoxide (DMSO) were used as positive and negative controls, respectively. Phytochemical screening revealed the presence of several secondary metabolites, including alkaloids, flavonoids, saponins, steroids/triterpenoids, and tannins in the Jatropha multifida leaf extract. The antibacterial assay demonstrated that the extract inhibited the growth of Pseudomonas aeruginosa, as indicated by the formation of inhibition zones around the discs. The diameter of the inhibition zones increased with increasing extract concentration, indicating a concentration-dependent antibacterial effect. Jatropha multifida leaf extract possesses antibacterial activity against Pseudomonas aeruginosa, which may be attributed to the presence of bioactive secondary metabolites. These findings suggest that the plant has potential as a natural source of antibacterial agents. Further studies are recommended to isolate and characterize the active compounds responsible for the antibacterial activity.